2020
DOI: 10.1002/ehf2.12567
|View full text |Cite
|
Sign up to set email alerts
|

Management of Heart Failure with Reduced Ejection Fraction after ESC 2016 Heart Failure Guidelines: The Linx Registry

Abstract: Aims In May 2016, a new version of the European Society of Cardiology (ESC) Guidelines for the management of heart failure (HF) was released. The aim of this study was to describe the management of HF with reduced ejection fraction after the publication of ESC Guidelines. Methods and results The Linx registry is a multicentre, observational, cross‐sectional study from 14 Catalan hospitals that enrolled 1056 patients with HF and reduced left ventricular ejection fraction (≤40%) from 1 February to 30 April 2017 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
1
10
0
4
Order By: Relevance
“…The Linx Registry, one of the most recent HF studies in Spain, also had a large sample of patients and was carried out in cardiology departments in Catalonia. In that registry, de Frutos et al [ 39 ] estimated that the prevalence of NYHA functional class II–IV in patients with HF and EF ≤ 40% was 85.5%, remarkably close to the estimate obtained in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…The Linx Registry, one of the most recent HF studies in Spain, also had a large sample of patients and was carried out in cardiology departments in Catalonia. In that registry, de Frutos et al [ 39 ] estimated that the prevalence of NYHA functional class II–IV in patients with HF and EF ≤ 40% was 85.5%, remarkably close to the estimate obtained in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…We consider that its use could imply several clinical benefits, especially in three scenarios. First, it would help its implementation in daily clinical practice, which until now has been slower than expected in different countries ( DeVore et al, 2018 ; Wachter et al, 2019a ; de Frutos et al, 2020 ). Selecting patients with a super-response could be particularly helpful in health systems where resources are limited ( Krittayaphong and Permsuwan, 2018 ; Kahn et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several independent studies have reported that the heart and potentially the kidney seem to be—in addition to the respiratory tract—a primary target of SARS‐CoV‐2 infections leading to clinical signs of myocarditis and heart failure 102–105 and potentially renal failure 106,107 . The RAAS is activated in heart failure patients and RAAS blockade is a clinical mainstay in the treatment of heart failure 108–110 In patients with severe pneumonia requiring intensive care treatment, there is a compensatory activation of the RAAS and sympathetic nervous systems, resulting in tachycardia and an elevation of systemic vascular resistance that may be deleterious in this setting 7 .…”
Section: Discussionmentioning
confidence: 99%